Correlation between Preeclampsia and Infant Low Birth Weight at Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia - Zuvarcan, Diaz Alifarizki; Putra, David Anggara; Martuti, Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Preeclampsia is a pregnancy complication with a triad of symptoms including high blood pressure, proteinuria, and tissue swelling as well as convulsions and coma. Preeclampsia in pregnant women can cause disruption in the supply of nutrients and oxygen to the fetus which can inhibit fetal growth and development (intrauterine growth restriction). In several similar previous studies, there were different variations in results which could be caused by multifactorial factors. This research was conducted to determine the relationship between preeclampsia in pregnant women and low birth weight babies by including confounding factors into the research. Subjects and Method: This was a retrospective case control study at Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia. A total of 120 live birth infants was selected using purposive sampling. The dependent variable was low birth weight (LBW). The independent variables were preeclampsia, maternal age, gestational age, parity, gemelli, anemia, and asthma. Data were collected from medical records of Dr. Moewardi Hospital from January to December 2022. The data were analyzed using a multiple logistic regression. Results: Preeclampsia increased LBW by 7.75 times compared to without preeclampsia, and this was a statistically significant (OR= 7.75; 95% CI= 2.77 to 21.71; p<0.001). In addition, there was a confounding variable of gestational age (OR= 18.47; 95% CI= 6.46 to 52.79; p<0.001). Conclusion: Preeclampsia increases LBW, and this is a statistically significant.